Microbiology of the food chain. Horizontal method for the determination of Vibrio spp. Enumeration of total and potentially enteropathogenic Vibrio parahaemolyticus in seafood using nucleic acid hybridization Part 2, (28th October 2020) - British Standards Institution,
No abstract available